Glycolysis and Fatty Acid Oxidation Inhibition Improves Survival in Glioblastoma - McKelvey, Kelly J.; Wilson, Erica B.; Short, Susan; Melcher, Alan A.; Biggs, Michael; Diakos, Connie I.; Howell, Viive M. (Frontiers in Oncology, 2021)
Glioblastoma is the most aggressive adult glioma with a median survival of 14 months. While standard treatments (safe maximal resection, radiation, temozolomide chemotherapy) have increased the median survival in favorable MGMT-methylated glioblastoma (namely ~21 months), a large proportion of patients experience a highly debilitating and rapidly fatal disease. This study examined glioblastoma cellular energetic pathways and blockade using repurposed drugs – the glycolytic inhibitor, dicholoroacetate (DCA), and partial fatty acid oxidation (FAO) inhibitor, ranolazine (Rano). Gene expression data shows that GBM subtypes have similar glucose and FAO pathways, and GBM tumors have significant up-regulation of enzymes in both pathways, compared to normal brain tissue (p<0.01). DCA and the DCA/Rano combination showed reduced GBM colony forming activity, and increased oxidative stress, DNA damage, autophagy and apoptosis in vitro. In the orthotopic Gl261 and CT2A syngeneic murine models of GBM, DCA, Rano and DCA/Rano increased median survival and induced focal tumor necrosis and hemorrhage. In conclusion, dual targeting of glycolytic and FAO metabolic pathways provides a viable treatment that warrants further investigation concurrently or as an adjuvant to standard chemoradiation for GBM.